Development of an Integrated Construction Management System for Building Estimation (Journal of Engineering, 2012)
Project management are still depending on manual exchange of information based on paper documents. Where design drawings drafting by computer-aided design (CAD), but the data needed by project management software can not be extracted directly from CAD, and must be manually entered by the user. The process of calculation and collection of information from drawings and enter in the project management software needs effort and time with the possibility of errors in the transfer and enter of information. This research presents an integrated computer system for building projects where the extraction and import quantities, through the interpretation of AutoCAD drawing with MS Access database of unit costs and productivities for the pricing and duration of tasks, then exported to MS Project and MS Excel. The system was developed by using Visual Basic and ActiveX automation technology for combining the above software. The system, also, can calculate quantities of materials. The system includes digitizer (on-screen takeoff) calculates the lengths and areas of the drawings to which the form of an image and scanned. The integrated system has been applied to case study, a storages building for hospital 260 beds. The results proved the effectiveness of the system for the conversion of information from the graphical form dwg to numerical formulas xlcx / xlc and mpp can be handled easily pleased and software are covered.